2019
DOI: 10.1002/psp.2233
|View full text |Cite
|
Sign up to set email alerts
|

Employment, education, and family: Revealing the motives behind internal migration in Great Britain

Abstract: Distinctions between internal migration and residential mobility are often formed with reference to assumed differences in motivation, with migration typically linked to employment and educational motives and shorter distance mobility to housing and family. Using geocoded microdata, this article reveals how employment‐led migration represents only a minority share (≈30%) of total migration events over 40 km. Family motives appear just as important, even at distances ≥100 km, with the desire to live closer to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 39 publications
0
41
0
1
Order By: Relevance
“…Firstly (dis)incentive is the employment structure of the host city. One major force that drives migrants to leave their hometown is the greater potential of job opportunities in a city (Liu & Shen, 2014;Thomas, 2019). Job opportunities are also crucial for settlement decision-making.…”
Section: Urban Economic (Dis)incentives Education and Migrants' Smentioning
confidence: 99%
“…Firstly (dis)incentive is the employment structure of the host city. One major force that drives migrants to leave their hometown is the greater potential of job opportunities in a city (Liu & Shen, 2014;Thomas, 2019). Job opportunities are also crucial for settlement decision-making.…”
Section: Urban Economic (Dis)incentives Education and Migrants' Smentioning
confidence: 99%
“…The importance of nonresident family has been further supported by the findings of recent studies of self‐reported motives for migrating. Using data for the United Kingdom, Australia, and Sweden, Thomas, Gillespie, and Lomax () found family‐related factors to be just as important as a primary motive for migrating as employment or educational concerns, while a more detailed study of the United Kingdom revealed desires to live closer to nonresident family/friends to be the most frequently cited family‐related submotive (Thomas, ).…”
Section: Introductionmentioning
confidence: 99%
“…His work reveals that the propensity to cite employment-related motives increases with distance while the propensity to cite housing-related motives decreases. While there are important differences in how distance and motives are reported and classified, broadly similar patterns have been found in studies looking at Australia (Clark and Maas 2015), Great Britain (Dixon 2003;Thomas 2019), New Zealand (Morrison and Clark 2011), and the United States (Geist and McManus 2012).…”
Section: Introductionmentioning
confidence: 62%